Prehypertension and hypertension among young Indonesian adults at a primary health care in a rural area (Faculty of Medicine Universitas Indonesia, 2013)
Background: Prehypertension and hypertension were related with many complications of nearly every organ, but often neglected by young adults in rural area. This research was done to observe the prevalence of prehypertension and hypertension among young adult in a primary health care of rural area at Cicurug, Sukabumi District, West Java. Methods: This cross-sectional study was done in Cicurug Public Health Center, Sukabumi District, West Java. The subjects were consecutively recruited from the outpatient clinic on Monday until Saturday in September 2012,18-25 years old, not pregnant nor having shock. They were interviewed about their age, gender, physical activity, sitting hours, smoking habit, alcohol consumption, and family history and examined by trained health professionals (weight, height, body mass index [BMI], systolic and diastolic blood pressure). Results: From 111 young adults, 34.2% had prehypertension and 17.1% had hypertension. Within sex groups, the prevalence of prehypertension was higher in females, whereas hypertension was occurred more in males. Neither of family history from mother nor father were associated with prehypertension and hypertension compared with normotension. Total activity was not associated with prehypertension (OR = 2.6; p = 0.052) and hypertension (OR = 1.758; p = 0.498). BMI was associated with hypertension (OR = 3.354; p = 0.041) and not associated with prehypertension (OR = 2.343; p = 0.099). Conclusion: Prevalence of prehypertension and hypertension were relatively high among young adult in primary health care of rural area. Intervention to prevent further complications needs to be done early with lifestyle modification because blood pressure is associated with modifiable risk factors, such as BMI and total activity. (Med J Indones. 2013;22:39-45) Keywords: Hypertension, prehypertension, rural area, young adult